Dietary acculturation and food habit changes among Chinese immigrants in Portugal - Li, Catarina (2023)
Chinese individuals who immigrate to a Western country tend to change their eating patterns and behaviors depending on how long they live in the host country. This is dietary acculturation, and it can have a positive or negative impact on eating habits. Thus, we aimed to characterize the dietary acculturation of the Chinese immigrant community in Portugal and check the trend of the direction of this acculturation. The study involved 213 immigrants and assessed food consumption, meal patterns, and dietary acculturation. A mean Western acculturation score of 70.1 ± 8.9. was identified and 71.4% had a high Western acculturation score. No one had low or very high Western acculturation. Participants who have a higher level of acculturation tend to have higher energy and fat intake. The likelihood of mixing meals, including, and combining, Chinese and Portuguese meals and foods are associated with time spent in Portugal. Efforts should be made to encourage Chinese immigrants to make a positive dietary transition during their acculturation process.